Male and Female Subpopulations of Salix viminalis Present High Genetic Diversity and High Long-Term Migration Rates between Them - Zhai, Feifei; Mao, Jinmei; Liu, Junxiang; Peng, Xiangyong; Han, Lei; Sun, Zhenyuan (Frontiers in Plant Science, 2016)
Dioecy distributed in 157 flowering plant families and 959 flowering plant genera. Morphological and physiological differences between male and female plants have been studied extensively, but studies of sex-specific genetic diversity are relatively scarce in dioecious plants. In this study, 20 SSR loci were employed to examine the genetic variance of male subpopulations and female subpopulations in Salix viminalis. The results showed that all of the markers were polymorphic (Na=14.15, He=0.7566) and workable to reveal the genetic diversity of S. viminalis. No statistically significant difference was detected between male and female subpopulations, but the average genetic diversity of male subpopulations (Na=7.12, He=0.7071) and female subpopulations (Na=7.31, He=0.7226) were high. Under unfavorable environments (West Liao basin), the genetic diversity between male and female subpopulations was still not significantly different, but the genetic diversity of sexual subpopulations were lower. The differentiation of the ten subpopulations in S. viminalis was moderate (FST=0.0858), which was conformed by AMOVA that most of genetic variance (94%) existed within subpopulations. Pairwise FST indicated no differentiation between sexual subpopulations, which was accompanied by high long-term migrate between them (M=0.73~1.26). However, little recent migration was found between sexual subpopulations. Therefore, artificial crossing or/and transplantation by cutting propagation should be carried out so as to increase the migration during the process of ex situ conservation.